Water Security as Shared Security Challenges? A Comparison of Kazakhstan and Uzbekistan Security Discourse towards the Aral Sea - Dharmaputra, Radityo (Global Strategis, 2018)
This article analyses the water security problems in Central Asia by comparing Kazakhstan’s and Uzbekistan’s policy regarding the Aral Sea. As one of the perpetual problem in Central Asia, the condition of freshwater resources in the Aral Sea has been worsening for the last decades. Efforts by governments were isolated and unorganised. Both the Kazakhstan and the Uzbek government, which had their own share of the problem, had been unable to cooperate on this issue. This article tries to elaborate the problem by using the theory on securitisation process, regional security complex, and the patterns of amity-enmity. This research finds that while the amity-enmity patterns was absent, the differing process of securitisation (in Kazakhstan) and de-securitisation (in Uzbekistan) had forced both states to embark on their own strategies and policies regarding the Aral Sea.